Fruit coat patterns and morphological properties of seven species of Symphytum L. (boraginaceae) from Turkey - Akçin, Öznur Ergen; Baki, Hilal (Bangladesh Journal of Botany, 2010)
<!–[if gte mso 9]> ZNUR 11.9999 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Micro- and macro-morphological characters of fruit surface of seven species of Symphytum L. in Turkey were investigated. Fruits of S. asperum Lepechin, S. sylvaticum Boiss., S. brachycaylx Boiss and S. kurdicum Boiss. & Hausskn have indistinct basal ring which in S. ibericum, S. orientale and S. bornmuelleri is distinct. Based on the structure and ornamentation of the fruit surface, tuberculate and rugose types can be distinguished. Micro-morphological characters could be useful in solving taxonomic problems of Symphytum asperum, S. kurdicum, S. ibericum, S. orientale, S. bornmuelleri, S. brachycalyx and S. sylvaticum. Key words: Symphytum L.; Boraginaceae; Fruit surface; Micromorphology; SEM; Turkey DOI: 10.3329/bjb.v38i2.5145 Bangladesh J. Bot. 38(2): 185-188, 2009 (December)